2010
DOI: 10.1007/s00384-010-1094-3
|View full text |Cite
|
Sign up to set email alerts
|

Management and outcome of colorectal anastomotic leaks

Abstract: Anastomotic leaks are not detected until late in the post-operative period and are associated with a high mortality. Demand on hospital resources is high. In this series, patients who leaked after a colonic anastomosis had a higher mortality and permanent stoma rate than after leaks from a rectal anastomosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
1
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 35 publications
1
51
1
3
Order By: Relevance
“…Anastomotic leakage is a serious complication after gastrointestinal surgery resulting in a significant increase in the 30-day mortality and morbidity rates. The mortality rate of this complication may be as high as 13-27% [1,2,3,4,5,6,7,8]. The reported anastomotic leakage rates are 1-39%, but a comparative evaluation of the studies is difficult due to the lack of standardized definitions [9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Anastomotic leakage is a serious complication after gastrointestinal surgery resulting in a significant increase in the 30-day mortality and morbidity rates. The mortality rate of this complication may be as high as 13-27% [1,2,3,4,5,6,7,8]. The reported anastomotic leakage rates are 1-39%, but a comparative evaluation of the studies is difficult due to the lack of standardized definitions [9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Anastomotic leakage may cause peritonitis or intra-abdominal abscesses. They may increase morbidity, mortality and the duration of hospitalization [13].…”
Section: Discussionmentioning
confidence: 99%
“…1,6 In addition to existing interventions used to decrease the risk of anastomotic leakage, such as altered surgical techniques, preoperative optimization, and different postoperative regimens, anastomotic coating has been suggested as a potential method.…”
mentioning
confidence: 99%
“…1,6 In addition to existing interventions used to decrease the risk of anastomotic leakage, such as altered surgical techniques, preoperative optimization, and different postoperative regimens, anastomotic coating has been suggested as a potential method. 7 Numerous experimental studies evaluating anastomotic coating have reported positive effects; however, contradictory results were found when the same coating material was evaluated by other researchers or in a different study design.…”
mentioning
confidence: 99%